CP-135 A clinical pharmacist's interventions in surgical patients in a large urban teaching hospital: a clinical and cost analysis. (25th February 2017) - Mullen, R; Carr, B; Berminghan, M
Abstract : Background: The role of the clinical pharmacist in the care of surgical patients has been largely under studied, both nationally and internationally. Surgical patients experience 2.0–27.7 adverse drug events per 100 admissions, of which 15.4–53.6% are preventable. No cost impact analysis conducted in the Irish setting has been done previously. Purpose: The aim was to ascertain the frequency and type of interventions made by a surgical pharmacist in a large teaching hospital in order to provide a quantitative value to this role. Material and methods: Design observational study of a single clinical pharmacist's interventions. All interventions made over a time period were recorded. Identify and classify interventions: medicines involved were categorised by Anatomical Chemical Therapeutic (ATC) classification and medication error type. Peer review: interventions were reviewed by a panel of five independent experienced healthcare professionals with assignment of risk ratings using the Dean and Barber visual analogue scale (VAS). Assignment of monetary values: costs potentially avoided were calculated by linking peer review results to values from a previously designed economic model by Campbell (eg, a mean VAS score of 7 was linked to a cost of €183.57). Results: 163 interventions were analysed for 87 patients with an acceptance rate of 97.6%. 1.23% of interventions were classified as minor (<3) with no patient harm anticipated. The majority, 97.54%, were classified as moderate to serious (3–7) with the potential to cause patient harm and cause increased length of hospital stay. 1.23% of interventions were classified as having the potential to cause severe harm (8–10). A cost benefit ratio of 10.6:1 was calculated, meaning €10.6 avoided for every €1 invested. The most common medication classes were analgesics, antithrombotics and drugs for acid disorders. Conclusion: This study details the frequency and types of interventions made by surgical pharmacists in terms of ATC classifications and medication error types. With peer review of all interventions along with assignment of monetary values to the costs avoided, the study provides a robust evidence base for the value of the surgical pharmacist. Further study of greater numbers and types of surgical patients would enhance findings. References and/or acknowledgements: Peer review panellists Dr Larry Bacon, Ms Sharon Byrne, Dr Tamasine Grimes, Mr Oisín O'hAlmhain and Dr Claire Thompson. No conflict of interest